PENGARUH DISCOVERY LEARNING MODEL BERBANTUAN MEDIA OBJEK LANGSUNG TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN OBSERVASI - Dewi, Ratna; Emidar, Emidar; Rasyid, Yulianti (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
This article was written to illustrate the effect of discovery learning models directly media-assisted objects and skills to write reports text of students of class VII SMP Negeri 11 Padang. Research data is the result of the score in the skill of writing the report text before and after using dicovery learning model assisted by direct object media. This study has three results. First, the skill of writing the report text of the seventh grade students of SMP Negeri 11 Padang before using discovery learning model with the object media directly in the qualification Self (C) with the average value 62.21. Second, the skill of writing the report text of the seventh grade students of SMP Negeri 11 Padang after using discovery learning model with the object media directly in the good qualification (B) with the average value 78,32. Third, based on the experiment concluded that there is a significant influence on the discovery learning model with the direct object of the students of class VII SMP Negeri 11 Padang because ttable<tcount (1,70<8,41).Â Kata kunci: pengaruh, discovery learning model, media objek langsung, menulis, teks laporan observasi